Aplikasi Edible Coating Berbasis Tepung Biji Nangka dan Alginat Terhadap Kualitas Buah Tomat - Ani, Alif Eva Mili; Mubarok, Ahmad Zaki; Murtini, Erni Sofia (Jurnal Teknologi Hasil Pertanian, 2024)
Enhancing post-harvest handling is crucial to boost productivity, preserve product quality, and enhance the competitiveness of food commodities. One effective approach to maintain product quality is by using edible coating, and in this case, alginate-based edible coating has been employed. The alginate-based edible coating exhibits a deficiency in terms of its inadequate mechanical properties. The addition of starch could improve the mechanical properties of alginate-based edible coating. Jackfruit seed starch has the potential to valorize as a cost-effective source of starch. Jackfruit seed flour has unique starch characteristics related to acid resistance, thermal properties, and mechanical properties when compared with starch from other sources. This study aims to optimize the concentration of alginate and jackfruit seed flour in the preparation of tomato edible coating using Response Surface Methodology (RSM). The effect of alginate concentration (1-2% b/v) and jackfruit seed flour concentration (1-2% b/v) on mass loss (%) and color difference (ΔE) were investigated. The optimum condition was obtained at an alginate concentration of 1.5% b/v and jackfruit seed flour concentration of 1.0% b/v with the resulting tomato quality value of mass loss of 5.43% and color difference (ΔE) of 0.70.